Synergistic effect of endurance training and nettle leaf extract on the IDO1-KYN-AHR pathway homeostasis and inhibiting of liver toxicity in rats with STZ-induced diabetes - Haghshenas, Rouhollah; Aftabi, Younes; Doaei, Saied; Gholamalizadeh, Maryam (Frontiers in Endocrinology, 2023)
Diabetes affects hepatic-molecular pathways including the kynurenine (KYN) pathway adversely. KYN is produced by indoleamine 2,3-dioxygenase (IDO) and works through aryl hydrocarbon receptor (AHR) activation. This study aimed to evaluate the effect of endurance training (EndTr) and nettle leaves extract (NLE) on the Ido1-KYN-Ahr pathway in the liver of rats with STZ-induced diabetes. Forty-eight rats were divided into 6 groups (Controls, EndTr, diabetics, diabetics treated with NLE (D+NLE), diabetics treated with EndTr (D+EndTr), and diabetics treated with EndTr+NLE). Rats performed the protocol of EndTr for eight weeks. The expressions of Ahr, Cyp1a1, and Ido1 were assayed using real-time PCR. Blood glucose level (BGL), liver malondialdehyde (MDA), and KYN levels, and AHR, CYP1A1, and IDO1 proteins were detected using ELISA. Expression of the genes and levels of MDA, KYN, and the proteins were significantly elevated (P<0.05). BGL and MDA significantly reduced in D+EndTr and D+NLE groups (P<0.05), however, EndTr+NLE showed significantly more decreasing effect (P<0.05). EndTr and EndTr+NLE reduced the KYN level significantly (P<0.05), however, NLE alone had no significant effect. Both EndTr and NLE reduced the Ahr expression and AHR level (P<0.05), however, D+EndTr+NLE had more reducing effect significantly (P<0.05). Neither EndTr and NLE nor D+EndTr+NLE had a significant lowering effect on CYP1A1 level, however, D+EndTr+NLE significantly reduced Cyp1a1 expression. Also, no significant effect was detected on Ido1, however, D+EndTr+NLE reduced the elevated level of IDO1 significantly (P<0.05). In conclusion, this study showed that the combination of EndTr and NLE may ameliorate the imbalanced Ido1-KYN-Ahr pathway in diabetic liver synergistically.